Associations of physical activity volume and intensity with depression symptoms among US adults - You, Jikai; Long, Jing; Wang, Zezhong; Yang, Yanan (Frontiers in Public Health, 2025)
BackgroundThis study aimed to investigate the associations of physical activity (PA) volume and intensity with the risk of depression symptoms.MethodsThe data utilized in this study came from the 2011–2014 National Health and Nutrition Examination Survey. PA was measured using a triaxial accelerometer and calculated using the Monitor-Independent Movement Summary (MIMS), MIMS units are a novel metric derived from wrist-worn accelerometer data, representing the intensity of PA for each minute across the entire monitoring period. PA volume and intensity were expressed by the average of daily accumulated MIMS (Daily MIMS) and peak 30-min MIMS (Peak-30MIMS; Peak 30-min intensity), respectively. Depression symptoms were defined as Patient Health Questionnaire-9 score ≥10. Weighted logistic regression and restricted cubic splines were used to evaluate the associations between PA metrics and depression symptoms.ResultsAfter adjusting for all covariates, higher Daily MIMS and Peak-30MIMS were associated with lower depression risk. Each additional 1,000 units in Daily MIMS and 1-unit in Peak-30MIMS were associated with a 5% [Odds ratio (OR) = 0.95, 95% confidence interval (95% CI): 0.94, 0.98] and 2% (OR = 0.98, 95% CI: 0.97, 0.99) reduction in depression risk, respectively. When including both MIMS metrics in the same model, the association between Peak-30MIMS and depression remained significant (p = 0.02), whereas Daily MIMS did not (p = 0.60). The spline analysis indicated a monotonic decrease in the OR with higher Daily MIMS values (P for non-linear = 0.21). An initial increase followed by a decrease in OR was observed with rising Peak-30MIMS values (P for non-linear <0.01).ConclusionOur findings indicate that higher PA volume and intensity are associated with lower depression risk. The association between PA volume and reduced depression risk was negated after adjusting for PA intensity in US adults.